The Cardinal Infant Ferdinand of Austria, Triumphal Entry in Ghent. Triumphalis Introitus Ferdinandus - Sos, Isabel Lloret (POTESTAS. Estudios del Mundo Clásico e Historia del Arte, 2018)
Abstract: In this article we are going to approach the significance of the Infant Cardinal Ferdinand of Austria Joyeuse Entrée in Ghent. He made different triumphal entries all around the territory as governor of the Netherlands and after his victory in Nördlingen, One of the most brilliant entries was dedicated to the city of Ghent, on January 26th in 1635. This entry is spoken about in the book, Serenissimi Principis Ferdinandi Hispaniarum infantis S.R.E. Cardinalis Triumphalis introitus in Flandriae Metropolim Gandavum. The author was the jesuit Guilielmo Becano. It was printed in Antwerp in 1636 in the printing press of Ioannis Meursi. Keywords: Joyeuse Entrée, Cardinal Infant, Nördlingen, Ghent, triumphal arches. Resumen: En este artículo nos acercaremos al significado de la Joyeuse Entrée gantesa del Cardenal Infante Don Ferdinand de Austria. Como gobernador de los Países Bajos y tras su victoria en Nördlingen, realizó diferentes entradas triunfales por todo el territorio. Una de las más brillantes fue la dedicada por la ciudad de Gante el 26 de enero de 1635. Esta entrada está recogida en el libro Serenissimi Principis Ferdinandi Hispaniarum infantis S.R.E. Cardinalis Triumphalis introitus in Flandriae Metropolim Gandavum. Su autor fue el jesuita Guilielmo Becano. Fue editada en Amberes en el año 1636 por la imprenta Ioannis Meursi. Palabras clave: Joyeuse Entrée, Cardenal Infante, Nördlingen, Gante, arcos triunfales.